El inconsciente colectivo y las Constelaciones Familiares - Hellinger, Bert (CIC. Cuadernos de Información y Comunicación, 2009)
The author exposes some basical laws of family constellations theory. He analyses interpersonal communication in family systems, in couple systems and in other primary relationships.L’auteur expose la base de la théorie des constellations familiales,. Il analyse la communication interpersonnelle dans la famille, dans le couple, et dans autres relations primaires.
Keywords: Hellinger; Family constellations theory; Orders of love; Interpersonal communication; Hellinger; Théorie des constellations familiales; Ordres de l’ Amour; Communication interpersonnelle